Clinical patterns and predictors of trauma-related mortality over 13 years: a retrospective analysis from a Level 1 National trauma center - Ayman El-Menyar; Sandro Rizoli; Ahammed Mekkodathil; Mohammad Asim; Sajid Atique; Abdel-Aziz Hammo; Hisham Jogol; Ahad Kanbar; Khalid Ahmed; Rafael Consunji; Husham Abdelrahman; Asmaa Al-Atey; et al. (World Journal of Emergency Surgery)
Abstract Background Qatar is one of six neighboring countries in the Gulf Cooperation Council region that form a political and economic alliance to foster multilateral cooperation. Given the shared challenges in trauma care, there is a need for a collaborative network to develop region-specific injury prevention strategies. For example, this study examines the clinical patterns and predictors of hospital mortality among trauma patients in Qatar. Methods A retrospective analysis of trauma-related deaths (2010–2023) was conducted. Patients were stratified into early hospital mortality (EHM, ≤ 48 h) and late hospital mortality (LHM, > 48 h) groups. Further analyses examined in-hospital mortality (24 h, 24–48 h, 3–7 days, and > 7 days), age groups, injury mechanisms, and severity. A multivariable regression analysis identified predictors of early mortality. Results Among 2,452 trauma-related deaths, 59% occurred in pre-hospital, while 41% occurred in-hospital. Compared to LHM (47%), EHM (53%) was associated with a younger age (35 vs. 39 years; p = 0.002), higher systolic blood pressure (0.82 vs. 0.67; p = 0.002), and diastolic blood pressure (2.03 vs. 1.75; p = 0.001). Motor vehicle crash (MVC) was the leading cause of death (35.3%), with vulnerable road users (VRU) the commonest in EHM (p = 0.004) and falls in LHM (p = 0.004). LHM was associated with a higher injury severity score (p = 0.001). On-admission systolic shock index independently predicted EHM (OR 2.23; 95% CI 1.09–4.52), while head (OR 7.14; 95% CI 2.44–20.00) and pelvic injuries (OR 3.70; 95% CI 1.19–11.11) and sepsis (OR 6.25; 95% CI 1.22–33.33) predicted LHM. In-hospital deaths exhibited a bimodal distribution, with peaks at 24 h (15%) and between the third and seventh days (10%). EHM showed an upward trend over the years (R² = 0.312), while LHM remained stable. Trauma-related mortality rates declined from 10.4 to 5.0 per 100,000 population (2011 and 2017) before rising to 9.7 by 2022. Pre-hospital deaths followed a similar pattern to the overall mortality, while the in-hospital rates remained steady. VRU-related injuries persisted at a high level, accounting for 26–43% of cases throughout the study period. Conclusion This study highlights distinct trauma-related mortality patterns, with EHM linked to hemorrhage and shock, while LHM is associated with severe head injuries and sepsis. These findings underscore the need for targeted interventions to optimize bleeding control and address predictors such as shock indices for EHM and head injuries for LHM.